The Amorites of the Ur III Period - Buccellati, Giorgio (1966)
= 28 text copies, 1 map, 7 charts; L.it. 8000; I. History of the Amorite Question; II. The Sources; III. List of Names; IV. Analysis of Amorite Names; V. Grammatical and Lexical Data from the Amorite Names; VI. Relationship between Old and Middle Amorite; VII. The Homeland of the Amorites; VIII. Geographical Distribution in the Sumerian Cities; IX. Social Stratification; X. Chronological Development; Appendix: New Texts.